Ultrarelativistic heavy-ion collisions - Vogt, Ramona (Elsevier, 2007)
This book is designed for advanced undergraduate and graduate students in high energy heavy-ion physics. It is relevant for students who will work on topics being explored at RHIC and the LHC. In the first part, the basic principles of these studies are covered including kinematics, cross sections (including the quark model and parton distribution functions), the geometry of nuclear collisions, thermodynamics, hydrodynamics and relevant aspects of lattice gauge theory at finite temperature. The second part covers some more specific probes of heavy-ion collisions at these energies: high mass thermal dileptons, quarkonium and hadronization. The second part also serves as extended examples of concepts learned in the previous part. Both parts contain examples in the text as well as exercises at the end of each chapter. - Designed for students and newcomers to the field - Focuses on hard probes and QCD - Covers all aspects of high energy heavy-ion physics - Includes worked example problems and exercises.